Age-stage, two-sex life table and predation parameters of Harmonia axyridis Pallas (Coleoptera: Coccinellidae), reared on Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae), at four different temperatures. (September 2022) - Islam, Yasir; Güncan, Ali; Fan, Yadong; Zhou, Xingmiao; Naeem, Afifa; Shah, Farhan Mahmood
Abstract: Pest management strategies relying on biocontrol agents may be altered by climate change because temperature regulates biological rates from individuals to populations. We investigated predation and development of Harmonia axyridis foraging on Acyrthosiphon pisum at four different temperatures (15, 20, 25, and 30 °C). Age-stage, two-sex life table analysis of the predator was conducted. Computer projections based on bootstrap percentile confidence intervals were used for assessment of population growth and predation parameters. H. axyridis development and predation varied across temperature. Development was much slower at 15 °C than at warmer temperatures. Pre-adult stage mean duration was 41.25 d at 15 °C, but this decreased to 28.67, 18.35, and 13.23 d at 20, 25, and 30 °C, respectively. The intrinsic rate of increase was 0.0805 d −1  at 15 °C, but this increased to 0.1009, 0.1324, 0.1813 d −1  at 20, 25, and 30 °C, respectively. The mean generation time ( T ) was 71.96 d at 15 °C, which decreased to 54.68, 42.64 and 29.96 d at 20, 25, and 30 °C, respectively. The highest intrinsic rate of increase ( r ) and finite rate of increase ( λ ) were obtained at 30 °C, while the highest fecundity occurred at 15 °C with 743.68 eggs/female. The net predation rates ( C 0 ) were 4445.28, 4299.30, 3602.18, and 2624.20 aphids at 15, 20, 25, and 30 °C, respectively. Population and predation projections were proportional to temperature. These results are useful for modelling the population response of H. axyridis to climate change and tailoring IPM strategies to altered climates. Graphical abstract: Image 1 Highlights: Effect of four constant temperatures was assessed on the predation and life table parameters of H. axyridis fed on A. pisum. The predator could develop, survive, and reproduce across all tested temperatures (15–30 °C). The intrinsic rate of increase and finite rate of increase were highest at 30 °C. The mean generation time and pre-adult stage were shortest at 30 °C. The net predation rate decreased with warming temperatures.